Banana sector: Agritrade Executive Brief Update 2013 - Technical Centre for Agricultural and Rural Cooperation; Eastern Africa Grain Council (Technical Centre for Agricultural and Rural Cooperation, 2013)
While cooking and brewing bananas are produced, consumed and traded in ACP countries, the dessert banana, Cavendish, is the predominant variety for international trade. Despite high production levels in Uganda, Rwanda and Burundi (mainly for local consumption) and a well established export market in Dominican Republic, Côte d’Ivoire and Cameroon (mainly to the EU market), the trade in dessert bananas is still dominated by Latin America. This Executive Brief presents the main developments of the banana market at global, EU and ACP levels, with special emphasis on the implications for ACP producers. As highlighted in the Brief, the Geneva Banana Trade Agreement (GBTA), the implementation of previously agreed free trade agreements (FTAs) and new FTAs (e.g. with India), and the budgetary constraints for the extension of EU banana accompanying measures (BAM) support are likely to threaten ACP banana export. However, new opportunities exist for ACP producers, such as the use of refrigerated containers in the supply chain, the growing demand for certified organic and fair trade bananas, and new market opportunities for processed added-value banana products such as flour and flour products.